Ambient pressure dried graphene aerogels with superelasticity and multifunctionality. Issue 38 (1st September 2015) - Yang, Hongsheng; Zhang, Tongping; Jiang, Min; Duan, Yongxin; Zhang, Jianming
Abstract : By an ice-template method, in this work we realized an ambient pressure dried graphene aerogel (ADGA) with superelasticity and multifunctionality by using ordinary instruments. Abstract : We report an ambient pressure dried graphene aerogel (ADGA) with superelasticity (rapidly recoverable from >90% compression) and multifunctionality that could be obtained with ordinary instruments by recasting a partially reduced graphene oxide hydrogel (PRGH) with an ice-template method. This study would be a key progress for realizing cost-effective and large-scale commercial production of high-performance graphene aerogels.